2017
DOI: 10.1021/acs.joc.7b02556
|View full text |Cite
|
Sign up to set email alerts
|

Group-Assisted Purification Chemistry for Asymmetric Mannich-type Reaction of Chiral N-Phosphonyl Imines with Azlactones Leading to Syntheses of α-Quaternary α,β-Diamino Acid Derivatives

Abstract: An asymmetric Mannich-type reaction between chiral N-phosphonyl imines and azlactones [oxazol-5(4H)-ones] has been established under convenient conditions at room temperature. The reaction was performed without using any bases, additives, or catalysts to achieve up to excellent chemical yields and diastereoselectivity for 32 examples. The α-quaternary syn-α,β-diamino acid products were purified simply by washing the crude mixtures with cosolvents, following the group-assisted purification chemistry/technology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…This chirality belongs to a type of Multilayer Organic Framework (M-LOF) of single organic molecules with pseudo C 2 -chiral characteristics. The key element of this chirality is characterized by three layers of planes that are arranged nearly in parallel fashion with one on top and one below the planar center as presented in Figure 1 This discovery was resulted from our Group-Assisted Purification (GAP) chemistry by taking advantage of Nphosphonyl imine reagents and their usage for asymmetric reactions (Figure 2(a), a-c) [41][42][43][44][45][46][47]. In this project, we found that chiral and achiral N-phosphonyl-or N-phosphinyl groups avoided the formation of oily and sticky products; instead, they afforded special crystalline solids that can be purified simply by washing crude products with common petroleum solvents without the use of column chromatography and recrystallization.…”
Section: Introductionmentioning
confidence: 99%
“…This chirality belongs to a type of Multilayer Organic Framework (M-LOF) of single organic molecules with pseudo C 2 -chiral characteristics. The key element of this chirality is characterized by three layers of planes that are arranged nearly in parallel fashion with one on top and one below the planar center as presented in Figure 1 This discovery was resulted from our Group-Assisted Purification (GAP) chemistry by taking advantage of Nphosphonyl imine reagents and their usage for asymmetric reactions (Figure 2(a), a-c) [41][42][43][44][45][46][47]. In this project, we found that chiral and achiral N-phosphonyl-or N-phosphinyl groups avoided the formation of oily and sticky products; instead, they afforded special crystalline solids that can be purified simply by washing crude products with common petroleum solvents without the use of column chromatography and recrystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Given the variety of different catalysis protocols to achieve asymmetric Mannich type reactions, [ 69 ] this methodology is without doubt one of the most versatile strategies to access the α,β‐diamino acid scaffold from simple starting materials. [ 7,70–85 ]…”
Section: β‐Amino Acid Derivativesmentioning
confidence: 99%
“…Accordingly, it comes as no surprise that they have also been heavily utilized for asymmetric Mannich‐type approaches to access chiral α,β‐diamino acid derivatives (Scheme 33). [ 7,75–77 ] A powerful asymmetric procedure was published in 2011 by Toste's group, who applied the L18 (AuOBz) 2 complex to control the asymmetric reaction between azlactones 12 and aldimines 57 . [ 75b ] Shortly after, Hui and co‐workers utilized the chiral phosphate‐based Ag‐catalyst C30 to carry out these Mannich reactions with very high enantioselectivities as well.…”
Section: β‐Amino Acid Derivativesmentioning
confidence: 99%
See 2 more Smart Citations